(untitled) (Research, Society and Development, 2023)
The wild passion fruit (Passiflora cincinnata Mast) is a species found mainly in the Caatinga, Cerrado and Atlantic Forest biomes. The fruits are marketed for consumption in natura or exploited by the industry to develop new products, generating co-products. The objective was to carry out the physical-chemical characterization and determine the content of bioactive compounds and antioxidant capacity of the passion fruit bark and seed, evaluating its nutritional and functional potential. Among the results obtained in the physical-chemical characterization, the ash content (1.24%) for the bark and the total lipid content (6.66%) for the seed (6.66%) stood out, in addition, both the bark fraction (3. 06 g.100 g-1) and the seed (1.00 g.100 g-1) showed low levels of reducing sugars. The peel had 28.07 mg.100 g-1 of vitamin C, 19.94 mg EAG.100g-1 of phenolic compounds and high antioxidant capacity (87.07%). In the seed, 17.12 mg EAG.100g-1 of phenolic compounds and also considerable antioxidant capacity (77.52%) were found. Thus, the characterization of wild passion fruit co-products, both in the peel and seed fraction, indicates nutritional, functional and technological potential for the development of new food products, contributing to the economy of the Brazilian semiarid region and reducing the environmental impacts resulting from food waste.